A) -6x+4=-8
B) 3(x+2)=2(x+4)
C) 7x-7=6-3(x+1)
Răspunsuri la întrebare
Răspuns de
0
-6x + 4 = - 8
-6x = -8 -4
-6x = - 12
x = -12 : 6
x = -2
3(x+2 ) = 2(x + 4 )
3x + 6 = 2x + 4
3x - 2x = 4 - 6
x = -2
7x - 7 = 6 - 3(x + 1 )
7x - 7 = 6 - 3x - 3
7x - 7 = 3 - 3x
7x + 3x = 3 + 7
10x = 10
x = 1
-6x = -8 -4
-6x = - 12
x = -12 : 6
x = -2
3(x+2 ) = 2(x + 4 )
3x + 6 = 2x + 4
3x - 2x = 4 - 6
x = -2
7x - 7 = 6 - 3(x + 1 )
7x - 7 = 6 - 3x - 3
7x - 7 = 3 - 3x
7x + 3x = 3 + 7
10x = 10
x = 1
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă